1994
DOI: 10.1590/s0036-46651994000100014
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni: the effect of dexamethasone on the cercaria-schistosomulum transformation, in vivo

Abstract: Treatment with dexamethasone (DMS) in the early phases of the experimental Schistosoma mansoni infection causes an indirect effect on the cercaria-schistosomulum transformation process. This is observed when naive albino mice are treated with that drug (50 mg/Kg, subcutaneously) and infected intraperitonealy 01 hour later with about 500 S. mansoni cercariae (LE strain). An inhibition in the host cell adhesion to the larvae, with a simultaneous delay in the cercaria-schistosomulum transformation, is observed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…As an advantage, peritoneal infection allows a simple and rapid method for mass screening of prophylactic agents to combat schistosomiasis (Pereira et al , 1974). This method of study has also helped to elucidate aspects of the early stages and immunology of the host–parasite relationship (Melo et al , 1978, 1980, 1993a, b, 1994; Melo & Pereira, 1980, 1985; Chao et al , 1986). Indeed, it has been demonstrated that parasites recovered from the peritoneal cavity of two albino mouse strains (AKR/J and Swiss) are significantly different in relation to the total body length of the worms, the intraperitoneal worm burden and the maturation degree of the schistosomes (Bicalho et al , 1993).…”
Section: Introductionmentioning
confidence: 99%
“…As an advantage, peritoneal infection allows a simple and rapid method for mass screening of prophylactic agents to combat schistosomiasis (Pereira et al , 1974). This method of study has also helped to elucidate aspects of the early stages and immunology of the host–parasite relationship (Melo et al , 1978, 1980, 1993a, b, 1994; Melo & Pereira, 1980, 1985; Chao et al , 1986). Indeed, it has been demonstrated that parasites recovered from the peritoneal cavity of two albino mouse strains (AKR/J and Swiss) are significantly different in relation to the total body length of the worms, the intraperitoneal worm burden and the maturation degree of the schistosomes (Bicalho et al , 1993).…”
Section: Introductionmentioning
confidence: 99%